2022
DOI: 10.1002/fam.3097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immersion time on the combustion characteristics of oil‐impregnated transformer insulating paperboard

Abstract: Transformer insulating paperboard is an insulating material commonly used in the oil-filled equipment in substations, which is usually immersed in the transformer oil.In this study, the effects of immersion time on the combustion characteristics of oil-impregnated transformer insulating paperboard are studied using the thermogravimetric, UL94 vertical flammability, and cone calorimeter experiments. The experimental results show that the total oil content increases with increasing immersion time and reaches the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition, mineral insulating oil is difficult to degrade and will cause ecological harm when it flows into the natural environment [3] . In contrast, the burning point of natural ester plant insulating oil is mostly above 360℃, which is a K-class difficult fuel, and it has a higher burning point than traditional mineral insulating oil [4] . Moreover, plant insulating oil has the advantages of being widely available, renewable, degradable, pollution-free, etc., which is expected to replace traditional mineral insulating oil [5] .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, mineral insulating oil is difficult to degrade and will cause ecological harm when it flows into the natural environment [3] . In contrast, the burning point of natural ester plant insulating oil is mostly above 360℃, which is a K-class difficult fuel, and it has a higher burning point than traditional mineral insulating oil [4] . Moreover, plant insulating oil has the advantages of being widely available, renewable, degradable, pollution-free, etc., which is expected to replace traditional mineral insulating oil [5] .…”
Section: Introductionmentioning
confidence: 95%
“…In 2021, Huang Qingdan used a cone calorimeter to carry out experimental research on the combustion characteristics parameters of plant insulating oil for transformers under different external radiant heat currents and concluded that the fire risk of plant insulating oil increased with the increase of external radiant heat flow. The order of fire risk from high to low was concluded: synthetic ester vegetable oil >> soybean oil > rapeseed oil > camellia seed oil [4] . However, the comparative analysis of mineral oil and natural ester insulating oil is still lacking, and so is the effect of initial fuel thickness on combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen [11] proposed that there were five main causes leading to transformer fire accidents, i.e., bushing malfunction, winding short circuit, iron core spoilage, deterioration of insulation oil quality and natural disasters. Additionally, the study of small oil pool fires was the most popular method to analyze the combustion characteristics of the transformer oil in terms of the initial oil temperature [6,12,13], the fire source power [14], the size of the oil pool [15][16][17][18][19], the level of oil pool [20], the burning rate [21], the ignition mode [22], the pulsating characteristics of the flame [23,24], etc. However, the transformer fire is a collection of multiple fire scenarios, and the burning rule obviously changes with its geometric scale.…”
Section: Introductionmentioning
confidence: 99%
“…Insulation oil is the main insulating and cooling medium for oil-immersed transformers, which are filled with large quantities of combustible transformer oil inside and on top of the oil pillow. Oil-immersed power transformers in the long-term operation process, its internal insulating oil paper will be affected by electrical, thermal, mechanical stress and other factors and gradually deteriorate, resulting in its insulation performance decline, in the fault, high temperature conditions fire, often leading to oil-immersed transformers themselves and other adjacent electrical equipment damage, serious damage to substations, once a fire will not only affect the safe and stable operation of the power grid, and even to the safety of society has a great impact [6][7][8][9][10][11][12]. In a 220kV transformer fire true type experiment, the temperature around the fire was up to 800℃, causing serious damage to the facilities around the substation [13].…”
Section: Introductionmentioning
confidence: 99%